Exploring the Role of Place Dependence, Identity, and Positive Experiences in Domestic Tourists’ Revisit Intention - Putri, Jellycha Mutiara Kurnia; Yudhistira, Putu Gde Arie (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2025)
Objective: This study investigates the role of place dependence and place identity in shaping domestic tourists' intentions to revisit beach destinations, focusing on the mediating effect of positive emotional experiences. Design/Methods/Approach: This study used a quantitative methodology with 314 respondents through an online questionnaire to collect data, which were then analyzed using PLS-SEM with SmartPLS 4. Findings: The findings indicate a significant positive influence of both place dependence and place identity on the intention to return, which is mediated by positive emotional experiences. Originality: In accordance with place attachment theory, this study highlights the significance of understanding the interconnection between place dependence and identity in building tourists' sense of attachment to specific destinations. Practical/Policy implication: To encourage repeat visits, it is crucial for stakeholders to preserve the destination's unique attributes and enhance the tourist experience through quality facilities, cultural events, and culinary and leisure activities. By offering exceptional experiences and high-quality services, stakeholders can foster long-term relationships with tourists and enhance a destination's appeal for future visits.